Detection of Intestinal Protists in an Urban Stream. Preliminary Research. - Estrada, Virginia; Saura, Alicia; Leone, Melisa; Enríquez, Gustavo; López Arias, Ludmila Sol (Sociedad Argentina de Microbiología Argentina (SAMIGE), 2022)
The District of Hurlingham is located in the suburbs of Buenos Aires and includes William Morris, Villa Tesei and Hurlingham cities. The territory shows neighborhoods with various urban consolidations, large areas of undeveloped land and has two watercourses that act as natural geographical limits: Morón stream and Reconquista River. In addition, it has a permanent surface watercourse that crosses the William Morris city called Soto stream. This tributary is highly contaminated chemical and microbiological due to industrial and residential effluents. Within the framework, from a research project on human intestinal parasitoses carried out in 2019 in the District of Hurlingham we found that 57% of 130 children under 12 years were parasitized. Protists were more frequent than helminths (85% vs 41%) and the most prevalent species were Blastocystis spp (26%), Enterobius vermicularis (23%), Giardia lamblia (13%) and Cryptosporidium spp. (7%). On the other hand, a socioenvironmental survey carried out on those responsible for the children revealed poor access to network water, sewage and environmental sanitation. The use of watercourses for recreational purposes was declared in 10% of the cases. Based on the aforementioned findings, the aim of this work was to detect and identify intestinal protist parasites from Soto stream samples. To do this, samples of surface water (5 liters) at no more than 50 cm depth and submerged plant leafs with noticeable biofilm formation were collected. In the laboratory, the water samples were kept immobile for 48 hours. After that time, the supernatant was filtered through a nitrocellulose membrane with a 1.5 µm pore and subsequently the retained particles were recovered. On the other hand, the sediment was concentrated by centrifugation. The plant leaves were washed with PBS and the biofilm was recuperated using a scalpel. The fractions (concentrates) were inspected by optical microscopy for protists detection and a modified Ziehl-Neelsen staining for coccidia detection was conducted. Likewise, fractions of the samples were inoculated in Jones medium and incubated under anaerobic conditions at 37°C for isolation of Blastocystis. Our results show the presence of similar structures to oocysts Cryptosporidium both in the water and in the biofilms samples. Besides, structures compatible with Blastocystis cells were isolated from the water samples. These preliminary results are consistent with the species detected in the examined children residing in the area. Complementary molecular studies will be performed to confirm the specific identity of the protists found in this study. The knowledge about parasitic species present in environmental matrices will allow the identification of new risk factors for the inhabitants of the community studied and will contribute to the development and implementation of comprehensive strategies for the prevention and control of intestinal parasites.
Trabajo presentado en el marco del XVII Congreso Argentino de Microbiología General (SAMIGE) realzizado los días 25-28 de noviembre, Los Cocos, Córdoba, Argentina)
Keywords: Ciencias médicas y de la salud::Ciencias de la salud::Parasitología